IGF-1-containing multi-layered collagen-fibrin hybrid scaffolds for bladder tissue engineering. (1st September 2016) - Vardar, E.; Larsson, H.M.; Engelhardt, E.M.; Pinnagoda, K.; Briquez, P.S.; Hubbell, J.A.; Frey, P.
Graphical abstract: Abstract: Clinical success of bladder reconstructive procedures could be promoted by the availability of functional biomaterials. In this study, we have developed a multi-layered scaffold consisting of a bioactive fibrin layer laminated between two collagen sheets all having undergone plastic compression. With this construct we performed bladder augmentation in a nude rat model after partial bladder excision and evaluated the morphological and functional behavior of the implant. The fibrin was functionalized with a recombinant human insulin-like growth factor-1 (IGF-1) variant that covalently binds fibrin during polymerization and has a matrix metalloproteinase-cleavage insert to enable cell-mediated release. The purified IGF-1 variant showed similar bioactivity in vitro compared to commercially available wild type (wt) IGF-1, inducing receptor phosphorylation and induction of human smooth muscle cell proliferation. In vivo, the multi-layered bioactive collagen-fibrin scaffolds loaded with the IGF-1 variant triggered dose-dependent functional host smooth muscle cell invasion and bundle formation with re-urothelialization 4 weeks after surgery in a rat model. Statement of Significance: The design of new bio-functional scaffolds that can be employed for bladder reconstructive procedures is a growing focus in the field of tissue engineering. In this study, a fibrin binding form of human insulin-like growth factor-1 (IGF-1) was produced and used to functionalize a multi-layered collagen-fibrin scaffold consisting of bioactive fibrin layer, sandwiched between two collagen gels. An effective dosage of our IGF-1 variant was successfully determined via a nude rat bladder model, which may play a critical role in estimating its therapeutic dosage in clinical trials. Thus, this new bioactive scaffold may offer an advanced approach to accelerate bladder regeneration.